Pharmacoepidemiology of stroke treatment in different hospitals - N. V. Mikheeva; O. V. Reshetko; L. G. Ryzhenkova (Фармакоэкономика, 2015)
cerebral infarction – is serious medical and social problem. Results of pharmacoepidemiological studies provide an objective assessment of the quality of pharmacotherapy of brain infarction, and find out the rational use of drugs and to identify ways to optimize the consumption of drugs. The results of pharmacoepidemiological analysis of drugs used for the treatment of cerebral infarction in hospitals of various types, are presented. An assessment of compliance with national and international recommendations «is carried out».